Standards vs. labels with imperfect competition and asymmetric information - Kenneth Baltzer (University of Copenhagen, Department of Food and Resource Economics (IFRO), 2011)
I demonstrate that providing information about product quality is not necessarily the best way to address asymmetric information problems when markets are imperfectly competitive. In a vertical differentiation model I show that a Minimum Quality Standard, which retains asymmetric information, generates more welfare than a label, which provides full information.
Keywords: L13; L15; L51; 330; minimum quality standard; label; asymmetric information; vertical differentiation; product quality